Renewable Energy Technologies: How technical curricula could enable a brighter future - Christine Winberg; Shairn Hollis-Turner (Environmental Association of Southern Africa, 2023)
The potential of renewable energy technologies to mitigate climate change while meeting the energy demand of future generations is recognised globally. In South Africa, occupations such as wind turbine technicians and solar photovoltaic installers are in high demand. In response to these needs, Renewable Energy Technologies (RET) subjects were developed as specialised electives within the Electrical Infrastructure Construction programme that is off ered by technical and vocational education and training (TVET) colleges. The focus of this study is the knowledge that underpins the RET subjects. The guiding research question is: What forms of knowledge underpin the RET curricula, and what is the relationship between these knowledge forms? The semantic dimension of Legitimation Code Theory was used to explain the knowledge forms underpinning the RET subjects. The study uncovered gaps and imbalances across the range of knowledge forms selected, while the relationships between the knowledge forms constrained cumulative knowledge building. The contribution made by the study is a principled understanding of how knowledge selection and sequencing in technical curricula could enable cumulative learning and build valued competencies within the renewable energy field.